(untitled) (Research, Society and Development, 2022)
The purpose of this study was to evaluate the level of knowledge of university students in Vitória de Santo Antão about syphilis. This is a cross-sectional exploratory research with a quantitative and qualitative approach, carried out with university students in Vitória de Santo Antão, Pernambuco, through the applications of a questionnaire. This questionnaire had 39 objective and 3 subjective questions to assess students’ level of knowledge about syphilis, estimating the prevalence of syphilis infection among students and relating the presence of infection to students’ socioeconomic and demographic conditions. The participants in this research demonstrated sufficient knowledge about syphilis knowing how to differentiate the three stages and how the infection is transmitted and prevented. Although most of the research participants declared that they did not use condoms in all the relationships they had, and that they had not been tested in the three months prior to the research, it was possible to observe that they have knowledge about the symptoms of each phase and the best forms of prevention. Although it was found that uneversity students’ knowledge about syphilis was sufficient from the analysis of the questionnaire responses, the need to promote awereness-raising actions and the construction of critical thinking regarding the implementation of safer sex could still be seen.